Understanding the mechanisms underlying the disruption of the blood–brain barrier in parasitic infections - Jamil Al‐Obaidi, Mazen M.; Mohd Desa, Mohd Nasir (John Wiley and Sons Inc, 2024)
Parasites have a significant impact on the neurological, cognitive, and mental well-being of humans, with a global population of over 1 billion individuals affected. The pathogenesis of central nervous system (CNS) injury in parasitic diseases remains limited, and prevention and control of parasitic CNS infections remain significant areas of research. Parasites, encompassing both unicellular and multicellular organisms, have intricate life cycles and possess the ability to infect a diverse range of hosts, including the human population. Parasitic illnesses that impact the central and peripheral nervous systems are a significant contributor to morbidity and mortality in low- to middle-income nations. The precise pathways through which neurotropic parasites infiltrate the CNS by crossing the blood–brain barrier (BBB) and cause neurological harm remain incompletely understood. Investigating brain infections caused by parasites is closely linked to studying neuroinflammation and cerebral impairment. The exact molecular and cellular mechanisms involved in this process remain incomplete, but understanding the exact mechanisms could provide insight into their pathogenesis and potentially reveal novel therapeutic targets. This review paper explores the underlying mechanisms involved in the development of neurological disorders caused by parasites, including parasite-derived elements, host immune responses, and modifications in tight junctions (TJs) proteins.